Values Clarification as a Reflective Practice for Preclerkship Medical Students - Lloyd Chen; Adrija Chaturvedi; Madeline McKenna; Mitchell Thom; Garrett Weskamp; Corinne Bazella; Oliver Schirokauer (Association of American Medical Colleges, 2023)
Introduction Values clarification is a structured, reflective process individuals engage in to better understand their own beliefs and priorities. We designed a workshop on values clarification to help preclerkship medical students anticipate and manage potential conflicts between their personal values and professional expectations. Methods We assigned participating students a values clarification exercise as prework. The 2-hour workshop included introductory remarks, a presentation by two physicians on personal ethical challenges they had faced, and faculty-facilitated small groups. In the small groups, students discussed moral discomfort in the context of various health care scenarios. Students were invited to complete an optional postworkshop survey with Likert-scale and short-answer questions. We analyzed the qualitative data and formulated 10 emerging themes. Results Thirty-eight of 180 participating students (21%) returned the survey. Of these, 30 (79%) agreed the workshop helped them appreciate that their values might come into conflict with professional obligations, 26 (68%) agreed they would be able to apply what they learned to future scenarios, and 30 (79%) agreed the workshop helped them understand their colleagues' values. The most prominent themes identified were that students found the physician panel especially meaningful and that the workshop helped students examine their own values and prepared them to better understand their future patients' values. Discussion Our workshop is unique in that it does not focus on a single area in health care but addresses moral discomfort broadly. To the best of our knowledge, it is the first values clarification curricular initiative developed for preclerkship medical students.